Prunus mira Koehne in Sichuan, China: Recorded History as a Medicine and Food, Modern Applications, Distribution, and Ethnobotanical Investigations - Zhang, Jingwen; Chen, Wanyue; Sun, Weijun; Zhou, You; Li, Xiaoli; Zhang, Jing; Fan, Gang; Yin, Hongxiang; Qin, Ju; Yuan, Yongcui; Xu, Wei; Wang, Zhang (Frontiers in Pharmacology, 2022)
Abstract: Prunus mira Koehne, a Prunus plant in the Rosaceae family, is named ཁམབུ། in Tibetan and “Guang he tao” in Chinese. It is mainly distributed in Tibet Tibetan Autonomous Region, Yunnan Province and Sichuan Province in China. It is also a rare “living fossil group” of peach genetic resources in the world. It is used in traditional Chinese medicine to treat dysmenorrhea, dysmenorrhea, injury, intestinal dryness, constipation and other diseases, and is used in Tibetan medicine to treat hair, eyebrows and beard shedding. It has the characteristics of fast growth, long life, drought tolerance and cold tolerance. In this paper, the botanical characteristics, medicinal history, modern applied research and application, ornamental value and ethnobotanical investigation of Prunus mira Koehne were recorded and evaluated. It is found that Prunus mira Koehne in Sichuan Province is mainly distributed in Ganzi Tibetan Autonomous Prefecture, and has certain economic and medicinal value. Prunus mira Koehne has high nutritional composition. It is made into high-quality edible oil, cosmetic base oil, fruit juice, fruit wine, fruit vinegar, ‘Liang guo” and other products with great market potential. The flowers of Prunus mira Koehne also have high ornamental value, which can create a tourism landscape of Prunus mira Koehne in Derong County, Ganzi Tibetan Autonomous Prefecture, Sichuan Province. Oleic acid and linoleic acid are the main fat soluble components of Prunus mira Koehne, which has medicinal value of anti-inflammatory and promoting hair growth. Its longevity and cold resistance can bring great genetic value and play an important role in maintaining peach gene diversity. Therefore, Prunus mira Koehne is very worthy of further research and development.